A interação segmento-sílaba nas líquidas, em Segredo-RS e a variação do /l/ na coda - Weber, Janaína Britto de Castro (2007)
This paper presents a description of the variable occurrences in the liquid system on the thirty people´s speach in a rural community of Segredo-RS. For this analysis we use the principles of the Sonority Cicle´s Theory (Clements, 1990) to the syllable and Traces’ Geometry (Clements and Hume, 1995) to the segments analisies. We analyse de coda variation of /l/ by anterior and posterior contexts, articulatory place and mode, and strengh of sylable as linguistic variables, and schoolling, sex and age as extralinguistics varibles, with VARBUL's program. The results demonstrated that the variable schooling associated with age was the social variable more determinant to the rotacization’s process, seeing that the less schooling are the oldier and they are the people that more apply the rotacization. The coda position in word was important in the rotacization’s production, this process occurred more in the medial coda. The youngest, more schooling, produced exclusively the dorsal semivocoid. In phonological therms, this research demonstrated that the variable obey an interaction between the syllable and the segment in a syllabic composition, like the Obligatory Contour Principle and the laws like the initial-syllable and final-syllable interfere in the speaking’s choice. The constraint [continuant] presents as the centre of many explanations in terms of the choice of segments and in the sonority scale’s discussion that it affects the onset and coda’s rotacization, but the wobble between alveolar point and dorsal point for trill. The palatal liquid conspicuousness in this variable realizations the advanced stage of the Fission, that reveals the delection of the consonant node to form a semivocoid for the less schooling speakers.